The primary surgical treatment of inguinal hernia: a changing trend towards laparoscopic hernioplasty - Govindaraj, Sridar; Roshini, A. P.; Prakash, Clement; B., Pavithra (International Surgery Journal, 2019)
Background: Inguinal hernias are the most common conditions presenting to the surgical department, which is repaired either with open technique or laparoscopically, Total Extra Peritoneal (TEP) or Trans-Abdominal Pre-Peritoneal (TAPP). Each procedure has its own advantages and drawbacks, none of them have been declared as the gold standard. Methods: Author did a prospective cohort study in a tertiary care hospital to assess the predictors and compare the outcomes for Open and Laparoscopic (TEP/TAPP) Inguinal hernia repair. A total of 180 patients were recruited into the study and followed up for a period of 1 year. Descriptive and inferential statistics was used to analyze the data. Results: 131 (72.8%) underwent open hernioplasty and 49 (27.2%) underwent laparoscopic hernioplasty. There was a significant difference between the time taken to complete an open and laparoscopic inguinal hernia repair (p=0.004), with laparoscopic repair taking lesser operating time. Laparoscopy was converted to open repair in 3 (6.1%) patients. Mean pain scores at 6-hours post-operative was 5.28±1.355 with no difference in the pain among patients who underwent open and laparoscopic repair. Seroma or hematoma are known complications, which was seen more in the open technique. The reason for choosing open surgery was secondary to the higher cost of laparoscopic repair (Adjusted Odds Ratio=0.168, p=0.004). Conclusions: The outcomes of laparoscopic inguinal hernia repair are comparable to that with the open repair.